Analytical stress–strain model of reinforced concrete masonry wallettes under axial compression. (December 2021) - Zahra, Tatheer; Thamboo, Julian; Asad, Mohammad; Song, Mengli
Abstract: The stress–strain characteristics of reinforced masonry (RM) under axial compression should be correctly understood to effectively analyse and design RM elements. However, past studies have overlooked this aspect and mainly focused on assessing the stress–strain behaviour of grouted or confined masonry. An experimental programme was executed in this research by constructing and testing RM wallettes under uniaxial compression to understand the stress–strain behaviour of RM. The effects of grout strength and lateral restrainer configurations on the compression behaviour were also studied. The experimental outcome revealed that the grout plays a major role in the axial capacity of the RM, while change in the configurations of the lateral restraining reinforcement did not significantly affect the axial capacities and axial stress–strain behaviour of RM wallettes. The predictability of the axial capacity of the RM wallettes were validated through the expressions given in the three masonry design standards. It was observed that all considered standards conservatively predicted the axial capacity of the RM. Moreover, the applicability of the existing analytical models in the literature for the RM were verified against the experimental data and an improved stress–strain model is proposed in this research.